2018
DOI: 10.1089/thy.2017.0607
|View full text |Cite
|
Sign up to set email alerts
|

The Prognostic Impact of Tumor Size in Papillary Thyroid Carcinoma is Modified by Age

Abstract: In our PTC cohort, the impact of tumor size on RFS was limited to patients aged ≥55 years. A single size threshold of 2 cm maximized prognostic discrimination with tumors >2 cm associated with a five times higher risk of recurrence than those ≤2 cm. These findings need to be validated in independent large cohorts and the potential management and staging implications further studied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
27
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(30 citation statements)
references
References 23 publications
1
27
0
2
Order By: Relevance
“…Although previous studies have identified the effect of tumor size on the risk of BM from RCC, our analysis revealed for the first time that age significantly affected the risk of developing BM from RCC and the impact of age was limited to patients with primary tumor size ≥ 7 cm. Tran et al [17] have also explored the interaction effect between tumor size and age on the prognosis of patients with papillary thyroid carcinoma and found that the impact of tumor size BioMed Research International on RFS was limited to patients aged ≥55 years. However, to our knowledge, there are no previous studies analyzing the interaction effect between tumor size and age on the risk of BM from RCC patients.…”
Section: Discussionmentioning
confidence: 99%
“…Although previous studies have identified the effect of tumor size on the risk of BM from RCC, our analysis revealed for the first time that age significantly affected the risk of developing BM from RCC and the impact of age was limited to patients with primary tumor size ≥ 7 cm. Tran et al [17] have also explored the interaction effect between tumor size and age on the prognosis of patients with papillary thyroid carcinoma and found that the impact of tumor size BioMed Research International on RFS was limited to patients aged ≥55 years. However, to our knowledge, there are no previous studies analyzing the interaction effect between tumor size and age on the risk of BM from RCC patients.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we found that patients with lower levels of serum Apo-A1 are more likely to be diagnosed with larger tumor sizes of PTC in a male cohort, especially in a young male subgroup (< 55 years old), this correlation was not seen when it comes to the female cohort. Tumor size has been demonstrated as an independent predictor of recurrence in PTC in previous study (tumors > 2 cm associated with higher risk of recurrence than those ≤ 2 cm ), [14] which indicates Apo-A1 is an protective biomarkers for male PTC patients.…”
Section: Discussionmentioning
confidence: 82%
“…In this study, we found that patients with lower levels of serum Apo-A1 and Lp (a) are more likely to be diagnosed with larger tumor sizes of PTC in a male cohort, especially in a young male subgroup (< 55 years old), this correlation was not seen when it comes to the female cohort. Tumor size has been demonstrated as an independent predictor of recurrence in PTC in previous study (tumors > 2 cm associated with higher risk of recurrence than those ≤ 2 cm ), [14] which indicates Apo-A1 and Lp (a) are two protective biomarkers for male PTC patients.…”
Section: Discussionmentioning
confidence: 84%